SPAM1 and PH-20 are two gene products expressed in bovine testis and present in sperm. Issue 6 (December 2018) - Saindon, Andrée-Anne; Leclerc, Pierre
Abstract : Sperm adhesion molecule 1 (SPAM1) is a sperm protein possessing a hyaluronidase domain in its N-terminus and a zona pellucida-binding domain in its C-terminus. Our previous studies showed that bovine spermatozoa potentially have 2 SPAM1 isoforms that present different C-terminal domains, different origins (testis and epididymis) and different locations in spermatozoa. In this study, two approaches were taken to characterize the different SPAM1 isoforms. First, 3′-RACE experiments were done to determine the sequence of the 3′ regions of the potential transcripts. Second, by in silico analyses, we aimed to determine whether our antibody that recognizes the N-terminal domain of SPAM1 detects two SPAM1 isoforms or two highly similar, although different, proteins. We found that the 3′ regions of SPAM1 transcripts from bovine testis and caput epididymis were identical. Nevertheless, two transcript variants that differ by 90 nucleotides, encoded by an entire exon, are expressed in both tissues. Only the protein encoded by the longest SPAM1 transcript variant was confirmed in ejaculated bull spermatozoa by mass spectrometry. In silico analyses revealed a highly similar protein to SPAM1, PH-20, that could potentially be recognized by our N-terminal antibody. The presence of PH-20 transcripts was confirmed in bovine testis and the protein is present in ejaculated spermatozoa. Our N-terminal antibody possibly recognizes both SPAM1 and the highly homologous protein PH-20 instead of two SPAM1 isoforms. Identifying the proteins implicated in the fertilization process is crucial in order to elucidate their roles and to better understand the complex process of fertilization.